A Laboratory Based Study On The Movement Of Radiocaesium In Some Soil Columns By Gamma Spectrometer (Journal of Bangladesh Academy of Sciences, 2012)
The fate and movement of 137Cs in different types of soil profiles of Chittagong City and Ishwardi Upazila of Bangladesh were investigated with laboratory based column method by γ-spectrometer. The diffusion coefficient, distribution coefficient and retardation factors of 137Cs were measured. The physio-chemical characteristics and radioactive concentration of natural radionuclides of the soil samples were also measured. The maximum diffusion coefficient was found 2.06 X 10-5 cm2/s in the investigated soils. The vertical movement of 137Cs in those soil samples found to be slow. Maximum of clay content corresponded with the maximum of retardation factor and with the minimum of diffusion coefficient. This experimental findings demonstrated that caesium is strongly absorbed in soil particles and therefore, do not pose any threat to ground water contamination by the approximated future accidental release of 137Cs in the study area. Moreover, the locally available clay can be used as an adsorbent for the decontamination of liquid radioactive waste generated at nuclear facilities without any pretreatment. Key words: Radioisotopes; Physio-chemical; Transport parameters; Soil column DOI: http://dx.doi.org/10.3329/jbas.v35i2.9417 JBAS 2011; 35(2): 141-151